Age-Related Disappearance of the Inhibitory Effect of Vascular Endothelium on Agonist-Induced Vasoconstriction in Rat Mesenteric Vascular Beds - Xin Jin; Yukiko Satoh-Otonashi; Yoshito Zamami; Narumi Hobara; Toshihiro Koyama; Pengyuan Sun; Simin Li; Yoshihisa Kitamura; Hiromu Kawasaki (Elsevier, 2009)
We previously reported that endothelium-derived hyperpolarizing factor (EDHF)- mediated response time-dependently suppressed methoxamine-induced vasoconstriction in mesenteric vascular beds isolated from 8-week-old rats. We investigated age-related changes in endothelial regulation of methoxamine-induced vasoconstriction. Mesenteric vascular beds isolated from young (8-week-old) to adult (16-week-old) rats were perfused, and changes in perfusion pressure induced by continuous perfusion of methoxamine or high KCl (60 mM) were measured over 180 min. In young preparations with intact endothelium, methoxamine-induced vasoconstriction time-dependently decreased to 20% of the initial levels, while time-dependent reduction was not observed in adult preparations. High KCl-induced vasoconstriction in young and adult preparations did not show time-dependent reduction. Endothelium removal abolished time-dependent reduction of methoxamine-induced vasoconstriction in young preparations and significantly attenuated vasoconstriction in adult preparations. Indomethacin, seratrodast, or tempol but not catalase significantly reduced methoxamine-induced vasoconstriction in adult preparations with endothelium. A23187 (Ca2+-ionophore)-, but not acetylcholine-, induced endothelium-dependent vasodilation in the presence of NG-L-nitro arginine methyl ether in adult preparations was significantly smaller than that in young preparations. These findings suggest that the inhibitory effect of mesenteric vascular endothelium on methoxamine-induced vasoconstriction disappears with aging by reducing EDHF and increasing endothelium-derived contracting factors and reactive oxygen species. Keywords:: aging, methoxamine-induced vasoconstriction, endothelium-derived hyperpolarizing factor, endothelium-derived contracting factor, rat mesenteric resistance artery